2011
DOI: 10.1111/j.1474-9726.2011.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Conserved cysteine residues in the mammalian lamin A tail are essential for cellular responses to ROS generation

Abstract: SummaryPre-lamin A and progerin have been implicated in normal aging, and the pathogenesis of age-related degenerative diseases is termed 'laminopathies'. Here, we show that mature lamin A has an essential role in cellular fitness and that oxidative damage to lamin A is involved in cellular senescence. Primary human dermal fibroblasts (HDFs) aged replicatively or by pro-oxidants acquire a range of dysmorphic nuclear shapes. We observed that conserved cysteine residues in the lamin A tail domain become hyperoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 58 publications
(75 reference statements)
4
89
0
Order By: Relevance
“…These findings are consistent with recent observations showing that oxidant exposure to lamin A thiols, as occurs during exposure to ROS or during cell senescence, results in lamin oxidation at conserved cysteines (Pekovic et al, 2011). Conversely, patients with LMNA mutations exhibit increased sensitivity to oxidative stress and show elevated ROS levels (Malhas et al, 2009;Pekovic et al, 2011;Richards et al, 2011;Sieprath et al, 2012). Lamin B1 also plays a role in oxidative stress; for example, lamin B1 expression decreases under conditions of chronic oxidative stress and this decrease alters the anti-oxidant protein expression through regulation of p53 or Oct-1 (Malhas et al, 2009).…”
Section: Mechanisms Involved In Lamin Aggregate Formationsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings are consistent with recent observations showing that oxidant exposure to lamin A thiols, as occurs during exposure to ROS or during cell senescence, results in lamin oxidation at conserved cysteines (Pekovic et al, 2011). Conversely, patients with LMNA mutations exhibit increased sensitivity to oxidative stress and show elevated ROS levels (Malhas et al, 2009;Pekovic et al, 2011;Richards et al, 2011;Sieprath et al, 2012). Lamin B1 also plays a role in oxidative stress; for example, lamin B1 expression decreases under conditions of chronic oxidative stress and this decrease alters the anti-oxidant protein expression through regulation of p53 or Oct-1 (Malhas et al, 2009).…”
Section: Mechanisms Involved In Lamin Aggregate Formationsupporting
confidence: 82%
“…Therefore, the presence of lamin aggregates in drug and geneticinduced liver injury models is likely related to the oxidative stress caused by accumulated PPIX. These findings are consistent with recent observations showing that oxidant exposure to lamin A thiols, as occurs during exposure to ROS or during cell senescence, results in lamin oxidation at conserved cysteines (Pekovic et al, 2011). Conversely, patients with LMNA mutations exhibit increased sensitivity to oxidative stress and show elevated ROS levels (Malhas et al, 2009;Pekovic et al, 2011;Richards et al, 2011;Sieprath et al, 2012).…”
Section: Mechanisms Involved In Lamin Aggregate Formationsupporting
confidence: 82%
See 1 more Smart Citation
“…In agreement with this model, it has recently been reported that the tail domain of lamin A is a target of oxidative damage, and its irreversible oxidation led to a loss of lamin A function and entry into senescence. 54 Oxidative stress is known to affect telomeres 55 and cause DNA damage; the increase in oxidative stress could therefore also be accountable Figure 1. Interplay between oxidative stress, telomere shortening, and DNA damage for the induction of senescence.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Reactive oxygen species (ROS) directly or indirectly oxidize the thiol group in cysteine residues, and thereby alter enzymatic functions (Kobayashi et al, 2006;Motohashi and Yamamoto, 2004;Pekovic et al, 2011;Rhee et al, 2005;Spickett et al, 2006;Winterbourn, 2008). The cytoplasm is normally maintained in a reducing state due to ubiquitous reducing reagents such as glutathione.…”
Section: Introductionmentioning
confidence: 99%